Tranexamic acid in emergency coronary surgery. Time for routine use? - Biskupski, Andrzej; Waligórski, Szymon; Kowalik, Bogdan; Żych, Andrzej; Brykczyński, Mirosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Aim of the study: To evaluate retrospectively the blood sparing effect and the side effects of prophylactic treatment with tranexamic acid in patients on antiplatelet medication (aspirin and clopidogrel) requiring emergency coronary surgery. Material and methods : Perioperative data on 120 patients consecutively operated on in our department from July 2009 until June 2010 for coronary artery disease on an emergency basis were analysed retrospectively. During the first 6 months 60 patients were operated on and received no antifibrinolytic treatment (control group). The next 60 patients (TA group) received tranexamic acid according to a new protocol implemented in January 2010. Mortality and morbidity including postoperative bleeding and blood and blood products usage were compared between the groups. Results : The demographic data and operative risk in both groups were similar. Postoperative drainage was lower in the tranexamic acid group (563.0 ml ±384.4 vs. 1047.1 ml ±1025.9 p < 0.05). The blood, fresh frozen plasma and platelet transfusion requirements were not statistically different between groups (blood 1.5 units ±2.1 vs. 2.5 units ±3.1, p = 0.07, fresh frozen plasma 1.1 units ±1.6 vs. 1.7 units ±2.7, p = 0.2, platelets 1.6 units ±2.6 vs. 1.4 units ±3.5, p = 0.3). There were no deaths in the tranexamic acid group and 4 deaths (6.7%, p = 0.04) in the control group. Myocardial infarction occurred in 3 (5%) and 10 (16.7%) patients respectively (p = 0.03). Cerebrovascular accidents occurred in 2 patients (3.3%) in both groups (p = 0.6). Two patients (3.3%) from the treatment group and 5 (8.3%) from the control group required re‑exploration for bleeding (p = 0.2). Conclusions : Perioperative prophylactic therapy with tranexamic acid reduces postoperative bleeding but does not influence the requirements for blood and fresh frozen plasma in patients undergoing emergency coronary artery bypass grafting. No increase in cardiac, neurological, respiratory or renal complications was noted.